2000
DOI: 10.1128/aem.66.9.3905-3910.2000
|View full text |Cite
|
Sign up to set email alerts
|

Starvation Improves Survival of Bacteria Introduced into Activated Sludge

Abstract: A phenol-degrading bacterium, Ralstonia eutropha E2, was grown in Luria-Bertani (LB) medium or in an inorganic medium (called MP) supplemented with phenol and harvested at the late-exponential-growth phase. Phenol-acclimated activated sludge was inoculated with the E2 cells immediately after harvest or after starvation in MP for 2 or 7 days. The densities of the E2 populations in the activated sludge were then monitored by quantitative PCR. The E2 cells grown on phenol and starved for 2 days (P-2 cells) surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 42 publications
4
39
0
Order By: Relevance
“…Furthermore, reduction growths of 55.4%, 65% and 30.5% was also observed in the loamy soil sample. This observation which is similar to the reports of previous studies [3,7,14] may be due to the toxic effect of the Lead metal on the strains and/or that the substrate in the soil is not bio-available to the organisms.…”
Section: Survival Patternsupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, reduction growths of 55.4%, 65% and 30.5% was also observed in the loamy soil sample. This observation which is similar to the reports of previous studies [3,7,14] may be due to the toxic effect of the Lead metal on the strains and/or that the substrate in the soil is not bio-available to the organisms.…”
Section: Survival Patternsupporting
confidence: 82%
“…However, many factors including predation, competition with indigenous microorganisms, nutrient availability, physicochemical parameters and other environmental factors necessary for growth has been found to influence the survival of bioaugmented microbes as well as their bioremediation efficiencies [1,2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drawback of this method is the possible reduction in the number of viable bacterial cells and subsequently the loss of biodegradation potential. The influence of a starvation process on the viability of degrading bacteria has been discussed controversially (50). Improved survivability has been reported (48), while another study found no significant effects on survivability (49).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a short starvation period of about 18 to 24 h was sufficient to reduce endogenous CO 2 production effectively. Extended starvation periods up to 10 days cause a significant decrease in respiration and dehydrogenase activity (50) and may also result in a decrease in biodegradation potential.…”
Section: Discussionmentioning
confidence: 99%